Women and school leadership. New prospects for educational leadership - Dello Preite, Francesca (Formazione & insegnamento, 2015)
The essay is about the issue of school leadership feminisation in Italy, a phenomenon of recent onset, still little studied and poorly available in scientific literature. Looking at studies on female leadership and Diversity Management, the intent is to discuss the possible transformations concerning educational leadership, generated by the increased number of female leaders, in order to promote educational research projects that could enhance processes of educational innovation through the empowerment of differences.